A Non-Isolated Extendable Boost Topology With Continuous Input and Output Currents - Hossein Gholizadeh; Alireza Poursalan; Reza Sharifi Shahrivar; Saeed Amini; Mohammadreza Salehi; Lazhar Ben-Brahim (IEEE Access)
This paper presents a new expendable boost DC-DC converter design with continuous input and output currents. The voltage gain and voltage-current stresses on the semiconductors are the same as those in the conventional boost converter. The proposed converter has lower conduction loss in the inductors compared to the traditional boost converter, resulting in greater efficiency across all duty cycle ranges and under identical conditions. Additionally, the maximum voltage gain in the new topology surpasses that of the conventional boost converter. The continuity of the output current eliminates the non-minimum phase behavior of the traditional topology of boost, making it faster than the conventional boost converter. A new family of converters is derived from the proposed topology. These newly suggested topologies have higher gains than the basic topology. The paper analyzes the proposed converter in both ideal and non-ideal modes, outlines the requirements for continuous conduction mode (CCM) operation, and investigates non-ideal voltage gain and efficiency sensitivity. The potential extensions of the proposed topology are discussed. Notably, all these extensions have a higher voltage gain while retaining all the advantages of the proposed primary topology. Simulation and experimental tests are carried out for the main topology. Moreover, the voltage gain tests based on experimental results are discussed for the extensions of the main topology and compared with their corresponding theoretical predictions. The results confirm the feasibility of the proposed converter.